Book review: Belyakov A.V. Uraz-muhammad ibn Ondan and Isinay Karamyshev son of Musayit. Experience of a joint biography - Nikolay S., Lapin (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
The review analyses the monograph "Uraz-Muhammed ibn Ondan and Isinei Karamyshev son of Musaits" by Russian historian A.V. Belyakov. Experience of joint biography" published in Kazakhstan by ABDI Company Publishers in 2019. Despite the genre of "joint biography" a noticeably larger volume of the monograph is devoted to biography of Kasimov khan and Kazakh sultan Uraz-Muhammed, in this connection the review focuses on biography of this historical figure directly connected with history of Kazakhstan. Some problems in the reconstruction of the biography of Uraz-Muhammad and his entourage are shown. Despite the limited array of sources that have survived to our days and directly related to Uraz-Muhammed A.V. Belyakov managed to reconstruct the main stages of the tsarevitch's life path. Of interest is the appendix to the work, which presents documentary materials related to the activities of the heroes of the book. In addition to the biography of the Tsarevich, the author managed to show the historical context in which the events unfolded, to a certain extent showing the environment in which not only Uraz-Muhammed himself, but also other numerous Chingizids who for various reasons found themselves in Russia at that time. Certain decisions and subjects related to the biography of the main character are of a debatable nature, but this does not prevent this book from being the most notable study of Uraz-Muhammad's life in modern historiography